2021
DOI: 10.1186/s12879-021-06882-2
|View full text |Cite
|
Sign up to set email alerts
|

RLEP LAMP for the laboratory confirmation of leprosy: towards a point-of-care test

Abstract: Background Nucleic acid-based amplification tests (NAAT), above all (q)PCR, have been applied for the detection of Mycobacterium leprae in leprosy cases and household contacts with subclinical infection. However, their application in the field poses a range of technical challenges. Loop-mediated isothermal amplification (LAMP), as a promising point-of-care NAAT does not require sophisticated laboratory equipment, is easy to perform, and is applicable for decentralized diagnosis at the primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…23−25 Four different RLEP sequences have been previously reported, namely, RLEP1, RLEP2, RLEP3, and RLEP4 (National Center for Biotechnology Information accession numbers FM211192.1, X17151.1, X17153.1, and X17152.1, respectively). 13 Additionally, RLEP genes have a high specificity and are widely used for leprosy diagnosis. 9,11− 13 The current study used RLEP2 as the target sequence for M. leprae detection, which is the core of the RLEP element.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23−25 Four different RLEP sequences have been previously reported, namely, RLEP1, RLEP2, RLEP3, and RLEP4 (National Center for Biotechnology Information accession numbers FM211192.1, X17151.1, X17153.1, and X17152.1, respectively). 13 Additionally, RLEP genes have a high specificity and are widely used for leprosy diagnosis. 9,11− 13 The current study used RLEP2 as the target sequence for M. leprae detection, which is the core of the RLEP element.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A reaction temperature of 65 °C is commonly used for Bst DNA polymerase. ,, Considering the high GC content of the target RLEP gene, we examined amplification temperatures in the range of 63–70 °C with 1 °C intervals to determine the optimal reaction temperature of the MCDA assay. Additionally, M.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The qPCR, 85 nested PCR 84 and variations such as multiplex, 87,91 duplex, 92 and droplet digital (ddPCR) 93 have been reported for different M. leprae target sequences, with RLEP and 16S rRNA representing the most used ones. [94][95][96] A study showed that multiplex PCR helps detect early leprosy cases and household contact surveillance for leprosy. 97 Nested PCR is useful for amplifying genes from samples with low bacillary load in PB patients, as this technique amplifies sequences within the amplicon generated in the first amplification round.…”
Section: Molecular Diagnosis Of Leprosy: State Of the Artmentioning
confidence: 99%